Profile of Pulmonary Tuberculosis Treatment in Inpatients with Covid-19 History Status at Pasar Minggu Regional General Hospital in May 2020-May 2021 - Yetri Elisya; Adin Hakim Kurniawan; Fikri Alamysah (Politeknik Kesehatan Kemenkes Jakarta II, 2021)
Pulmonary tuberculosis (TB) causes it by Mycobacterium tuberculosis, which attacks the respiratory system. During soaring cases of the Covid-19 virus outbreak, TB patients must be more aware of themselves from the episode. GTN (Global Tuberculosis Network) describes that out of 49 patients with TB status, around 26 patients suffered from pulmonary TB and were exposed to Covid-19. This study aims to determine the Profile of Pulmonary Tuberculosis Treatment in Inpatients with Covid-19 History Status at Pasar Minggu Regional General Hospital for the May 2020-May 2021 Period. This research method is a quantitative descriptive analysis with a retrospective method, taking primary data from records—patient medical. There were a total of 22 patients. Most of the sexes were male, namely 12 people (54.55%). The age of the most patients was > 60 years with a total of 6 people (27.27%), and the weight of the most patients was 38-54 kg with a capacity of 11 people (50%). The most common patients were new patients, with ten people (45.45%). The most category of treatment was Category II, with 12 people (54.54%). The pattern of KDT (Fixed-Dose Combination) category one that was most widely prescribed was the pattern of 3 4KDT tablets, three 2KDT tablets, four 4KDT tablets, and four 2KDT tablets having the same proportion of 4 prescriptions (18.18%). The most prescribed pattern of KDT category 2 was three tablets of 4KDT + 750 mg of streptomycin injection and three tablets of 2KDT + 3 tablets of ethambutol with nine prescriptions (40.90%). Drugs for Covid-19 patients are most often prescribed together with OAT, namely vitamins and minerals, as many as 56 prescriptions (42.42%).